INTERACTION AND NASIONALISM OF MILLENNIAL GENERATION IN THE NOVEL HOW TO LOVE INDONESIA BY BUMA M. SEMBIRING (INTERAKSI DAN SIKAP NASIONALIME GENERASI MILENIAL DALAM NOVEL HOW TO LOVE INDONESIA KARYA BUMA M. SEMBIRING) - Dzul Asfi Waraihan; Purwati Anggraini (Universitas PGRI Sumatera Barat, 2021)
The process of interaction should encompass good ethicand behavior asboth ethic and behavior are involved as controlsinperforming actions or utteringwords when interacting with others. Interaction in society can be used as an indicator to measure one's nationalistic attitude. The purpose of this research is to describe the tendency of the main character's behavior in their social interaction with other characters and examine both good and bad impacts received by the main character as a reflection of how to be socially friendly as stated in the novel How to Love Indonesia in the context of realizing the attitude of millennial generation nationalism. This research used descriptive qualitative method. The object of this research was the novel ‘How to Love Indonesia’ by Buma M. Sembiring. The research data were in the forms of units of stories or quotations in the novel. The data collection techniques comprised the stages of reading, recording, and analysis. The Sociology of Literature approach was carried out to analyze the data. The findings of this study described various behavioral tendencies of the main character in their social interaction. Politeness, not underestimating others, respecting the feelings of others, being humble, honesty and not offending others are behavior that any person needs to uphold in order to be accepted by the community, as well as an indicator of the nationalism of figures as a millennial generation.